Efektivitas Pelatihan Mindfulness Dengan Pendekatan Spiritual Terhadap Peningkatan Psychological Wellbeing Penderita Diabetes Mellitus Tipe 2 - Jayanti, Rina, Dr. Moordiningsih, M.Si, Psi, Rini Lestari, M.Si., Psikolog (2016)
Abstract. This study was conducted to determine the effectiveness of mindfulness training with a spiritual approach for improving the psychological wellbeing of people with diabetes mellitus type 2. The variables used in this study consisted of a free variable mindfulness training with a spiritual approach and callisthenics for patients with diabetes mellitus; and the dependent variable, which is the psychological wellbeing. The subjects were patients with type 2 diabetes mellitus. This research method is experimental research, with the design non-equivalent group design, pre-test - post-test control group design, consisting of the experimental group and the control group which were not selected randomly. Researchers used 33 participants were divided into 3 groups: the experimental mindfulness training group with a spiritual approach (KE 1), the experimental group 2 (KE 2) and the control group (KK). The analysis of data used the Friedman test KE 1, and it was determined there are significantly different levels of psychological wellbeing by chi square 14.114; asymp sig 0,001;p < 0,05. The increase occurred in 4 aspects of psychological wellbeing: autonomy, environmental mastery, personal growth, and purpose in life. The analysis of data on the KE 2 using the Friedman Test determined significant differences of psychological wellbeing with chi square 14.308; asymp.sig 0,001; p < 0,05. The increase occurred in one aspect of psychological wellbeing: selfacceptance. 3 different test groups used Kruskal Walis, and the post-test measurement data obtained was Chi Square of 8.075 with Asymp. Sig of 0,018; p < 0,05. Follow up measurement: Chi Square of 9,552 with Asymp.Sig of 0,008; p < 0,05. Mean rank post-test data KE 1 of 19,94 KE 2 of 12.20 and KK of 9,56. Follow up mean rank data KE 1 of 20,61 KE 2 of 11,40 and KK of 9,81. Mindfulness training with a spiritual approach more effectively improved the psychological wellbeing than callisthenics in patients with type 2 diabetes mellitus. Keywords: mindfulness training with a spiritual approach, callisthenics for diabetes mellitus, psychological wellbeing.